Real-Time Air Quality Index App: The Use of eWeather HDF App for Education in Monitoring of Pollutants and Meteorological Parameters in Nigeria - Francis Olawale Abulude; Matthew Ojo Oluwafemi; Kikelomo Mabinuola Arifalo; Jamok Jacob Elisha; Abdulrasheed Yusuf (ASEAN Journal of Science and Engineering Education, 2022)
The veracity of data derived from networks of low-cost measuring instruments is a rapidly increasing and contentious issue. For air quality monitoring, networks of low-cost devices, satellite modeling, and phone apps have risen to prominence. We used the eWeather HDF phone app to monitor the air quality (AQI, PM2.5, PM10, NO, NO2, CO, SO2, and meteorological parameters) of five Nigerian towns in this study. This app also can be used for education. The results show that the AQI of all towns is between 51 and 100. Except for Zaria, where the PM2.5 levels are about 16 percent higher, all of the locations' PM2.5 levels are within the World Health Organization (WHO) daily limit standard. Similarly, the PM10 level in the same town was nearly three times higher than the limit. NO2 (Akure Ilorin Ikere-Ekiti Zaria Ibadan), SO2 (Akure Ilorin Ikere-Ekiti Zaria Ibadan), CO (Zaria Akure Ilorin Ikere-Ekiti Zaria Ibadan), NO (Akure Ilorin Ikere-Ekiti Zaria Ibadan). Correlations with meteorological parameters are significant. Although the pollution levels in these towns are allowable, they may pose a risk to some individuals, especially those who are exceptionally sensitive to environmental changes.